Prehospital Double Defibrillation for Refractory Ventricular Fibrillation: A Scoping Review Protocol - Miraglia, Dennis (J Innov Card Rhythm Manag, 2020)
Double defibrillation (DD) has been proposed as an alternative treatment for patients with refractory ventricular fibrillation/pulseless ventricular tachycardia (VF/pVT) out-of-hospital cardiac arrest (OHCA) nonresponsive to the best current standard of care. Treatment results are promising, but the efficacy and safety of the procedure remain unclear. Currently, there is a paucity of evidence in the literature on DD suggesting the optimal strategy for treating this challenging patient population. Thus, we aim to perform a scoping review to explore the current literature addressing resuscitative parameters, survival rates, and neurological outcomes in refractory VF/pVT OHCA patients treated with DD as well as to identify gaps in the literature that may require further research. Here, we discuss the anticipated study protocol.